Restorative Justice dalam Penanganan Kekerasan Dalam Rumah Tangga: Analisis Integratif Hukum Positif dan Hukum Islam di Wilayah Hukum Polres Bungo - Lenny Maryani S; Abdul Halim; Risnita Risnita (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Domestic violence (DV) remains a complex legal and social problem, threatening family stability and human dignity. Although Law No. 23 of 2004 concerning the Elimination of Domestic Violence provides strict sanctions, conventional punishment methods are often considered ineffective in restoring damaged social relationships within families. This study examines the implementation of restorative justice in resolving domestic violence cases within the Bungo Police jurisdiction, from the perspective of positive law and Islamic law. This study uses an empirical legal approach and a sociological perspective, with primary data collected through interviews with investigators from the Women and Children Protection Unit (PPA), as well as secondary data from laws, police regulations, and related academic literature. The results show that restorative justice has been applied to several domestic violence cases during the investigation stage through mediation and peace agreements between the parties involved. This method helps reduce the backlog of cases, accelerates dispute resolution, and maintains family social stability. However, challenges remain, such as the possibility of re-victimization due to the imbalance of power between victims and perpetrators. From an Islamic legal perspective, restorative justice is in line with the principles of ta'zīr and maqāṣid al-sharī'ah, especially the preservation of human dignity, life and offspring. By guaranteeing the protection of victims and preventing repeated violence, restorative justice can be an additional mechanism in cases of domestic violence.